Identidade negra, autoralidade e paratopia no discurso constituinte literário de Joel Rufino dos Santos - Oliveira, Jonatas Eliakim D Angelo de (2023)
In this thesis, we study the concepts of enunciative identity, authorality and paratopia and the emergence of a black enunciator in Joel Rufino dos Santos' literary discourse. With an analysis of the discursive production, we aim to verify how the enunciative identity emerges in the paradoxical relations that the author establishes with his speech, identifying the aspects and factors that contribute to the characterization of the paratopia inherent in the process of literary creation. For that, we make use of the theoretical-methodological postulates of the French Discourse Analysis, more specifically, in the enunciative-discursive perspective of Dominique Maingueneau. In the literary discourse of Joel Rufino dos Santos, images of black men and women are built in opposition to the white colonizer man, due to the emergence of an identity that tells the story of enslavement and black people from a new perspective. The black person ceases to occupy the place of object to assume the role of subject, since the paratopic condition of the author can be considered as an intrinsic factor to his artistic-literary creation process, understood as what nourishes the activity of discursive production. Thus, in the literary discourse of Rufino dos Santos, a black subject emerges, who assumes the role of protagonist in his own history, resisting the history imposed on him and establishing new paradigmatic bases for the future